Evaluation of demineralization adjacent to orthodontic bracket and bond strength using fluoride-releasing and conventional bonding agents - Siddharth D Lodaya; K M Keluskar; Vijay Naik (Wolters Kluwer Medknow Publications, 2011)
Background and Objectives: One of the most difficult problems encountered in orthodontic treatment with fixed appliance is the control of enamel demineralization around the brackets. Fluoride-releasing bonding adhesives were introduced to aid in the prevention of demineralization adjacent to orthodontic brackets. Hence, an in vitro study was conducted to evaluate and compare demineralization adjacent to the orthodontic bracket and the bond strength using fluoride-releasing adhesive and conventional adhesive. Materials and Methods: One hundred and twenty healthy extracted premolars were selected for the study and were divided into two groups, each group consisting of 60 teeth. Both groups were further divided into three subgroups consisting of 20 samples each. Samples of subgroups A and B were bonded with two prototypes of fluoride-releasing adhesives (i.e. Rely-a-bond and Tru-bond). Samples of subgroup C (ortho-one) were bonded with conventional non-fluoride-releasing adhesive. Group I samples were subjected to demineralization in an acidic medium (methyl cellulose buffered with acetic acid at a pH of 4.5) for 4 weeks, which were later observed under a stereomicroscope. Group II samples were tested for shear bond strength using the Instron Universal testing machine. Results: Both fluoride-releasing adhesives showed statistically significant lower enamel demineralization around the bracket when compared with the conventional adhesive. There was no statistically significant difference on comparing the demineralization between the two prototypes of fluoride-releasing adhesive. Evaluation of shear bond strength revealed that there was no significant difference between the subgroups. Conclusion: Fluoride-releasing adhesives might aid in the prevention of demineralization adjacent to the orthodontic bracket with acceptable bond strength.